Perencanaan Jangka Pendek DAS dengan Metode Perhitungan Erosi Kuantitatif dengan Penginderaan Jauh dan Sistem Informasi Geografis - Beny Harjadi (Fakultas Kehutanan Universitas Gadjah Mada, 2008)
Short-term Planning of Watershed Using Calculation of Quantitative Erosion Method Based on Remote Sensing and Geographic Information SystemPriority determination of some sub watersheds experienced difficulties based on the fact that data collection of the related sub watersheds takes time and quite costly. Whereas to comprehensively manage sub watershed, some prioritizet sub watersheds have to be chosen to manage holistically and integrally with good coordination between some related agencies. The study was carried out in India in two Nawagaon Maskara Raoi watersheds, Saharanpur city, located 250 km to the east of New Delhi. The study appointed a sub watershed to be the prioritu among the other 10 available using quantitative calculation method (MMF: Morgan, Morgan, and Finney method). The research aimed to measure the quantitative erosion based on MMF model and calculate the value index to determine the priority in sub watershed.The erosion calculation by MMF model produced five erosion levels i.e. very low (vl=0-5t/ha/yr), low (l=5-10 t/ha/yr), medium (m=10-25 t/ha/yr), high (h=25-50 t/ha/yr), and very high (vh 50 t/ha/yr). At the highest erosion level (vh) location with the most extensive land damage to the narrowest respectively was Sarbar Rao (SB) = 116.84 ha, Galr Rao (GR), Sahansra Thakur (ST), Shakumbari Rao (SH), Khawonwala Rao (KH) Kahan Rao (KR), Nawagaon Rao (NW), Chamarla Rao (CH), Track Fallows (TF), Barkala Rao (BR), and Maskara Rao (MR) = 0.34 ha. Of 11 sub watershed, priority value index was calculated, and the highest value (main priority) to the lowest one (least priority) is respectively as follows: GR (Galr Rao) = 33,5, KR (Kahan Rao), ST (Sahansra Thakur), TF (Track Fallows), BR (Barkala Rao), SB (Sarbar Rao), SH (Shakumbari Rao), CH (Chamarla Rao), KH (Kharonwala Rao), MR (Maskara Rao), and NW (Nawagaon Rao) = 18,2. Therefore the main priority fell for sub watershed Galr Rao (997.32) and the least priority for watershed Nawagaon Rao (7646.78 ha).